Radioactive Beams for Image-Guided Particle Therapy: The BARB Experiment at GSI - Boscolo, Daria; Kostyleva, Daria; Safari, Mohammad Javad; Anagnostatou, Vasiliki; Äystö, Juha; Bagchi, Soumya; Binder, Tim; Dedes, Georgios; Dendooven, Peter; Dickel, Timo; Drozd, Vasyl; Franczack, Bernhard; et al. (Frontiers in Oncology, 2021)
Several techniques are under development for image-guidance in particle therapy. Positron (β+) emission tomography (PET) is in use since many years, because accelerated ions generate positron-emitting isotopes by nuclear fragmentation in the human body. In heavy ion therapy, a major part of the PET signals is produced by β+-emitters generated via projectile fragmentation. A much higher intensity for the PET signal can be obtained using β+-radioactive beams directly for treatment. This idea has always been hampered by the low intensity of the secondary beams, produced by fragmentation of the primary, stable beams. With the intensity upgrade of the SIS-18 synchrotron and the isotopic separation with the fragment separator FRS in the FAIR-phase-0 in Darmstadt, it is now possible to reach radioactive ion beams with sufficient intensity to treat a tumor in small animals. This was the motivation of the BARB (Biomedical Applications of Radioactive ion Beams) experiment that is ongoing at GSI in Darmstadt. This paper will present the plans and instruments developed by the BARB collaboration for testing the use of radioactive beams in cancer therapy.